2020
DOI: 10.3889/oamjms.2020.3388
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Muscle Invasion in Bladder Cancer with Cell Adhesion Properties and Oncoprotein Overexpression Using E-Cadherin and HER2/neu Immunohistochemical Markers.

Abstract: BACKGROUND: Most of bladder cancers are proven to be of urothelial origin (transitional cell carcinomas). Above 75% of them are of non-muscle invasive bladder cancer (NMIBC) type at presentation and the remainder are MIBC. Recent studies suggest that both are most probably two different categories based on both the histopathological and molecular features. The comprehensive understanding of the biomarkers expression in both categories will help in understanding the molecular event underlying each of them and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
1
0
0
Order By: Relevance
“…Similarly, the decreased E-cadherin expression was high significant in high grade than in low grade (P=0.002). Esmail et al [31] agree with our results who found that E-cadherin showed positive expression in 65% (13 case) of non-muscle invasive bladder cancer group and in 10% (2 cases) of the muscle invasive bladder cancer group, with high statistical significance (p<0.001).…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, the decreased E-cadherin expression was high significant in high grade than in low grade (P=0.002). Esmail et al [31] agree with our results who found that E-cadherin showed positive expression in 65% (13 case) of non-muscle invasive bladder cancer group and in 10% (2 cases) of the muscle invasive bladder cancer group, with high statistical significance (p<0.001).…”
Section: Discussionsupporting
confidence: 93%